Comparison of core muscle strengthening exercise and stretching exercise in middle-aged women with fibromyalgia: A randomized, single-blind, controlled study. Issue 50 (17th December 2021) - Park, Hyeng-Kyu; Song, Min-Keun; Kim, Dong-Joo; Choi, In-Sung; Han, Jae-Young
Abstract: Background: Many studies have reported that exercise is effective for fibromyalgia and various types of exercise are recommended. However, most of exercises lack evidence for fibromyalgia symptoms. We aimed to examine the effect of core muscle strengthening exercise compared to general stretching exercise in fibromyalgia patients. Methods: Forty fibromyalgia patients were enrolled. They were provided exercise program twice a week for 4 weeks: core muscle strengthening exercise and general stretching exercise. Outcome measures were Visual Analogue Scale, Borg Scale, fibromyalgia impact questionnaire (FIQ), widespread pain index, Symptom Severity Scale (SS), and balance scale and measured before and after exercise program. Balance function was assessed by checking the distance of sway on soft pad with eyes open (EO) and with eyes closed (EC). Results: After program, FIQ, SS, EO, and eyes closed showed statistically significant differences in the strengthening group while Visual Analogue Scale, Borg scale, FIQ, widespread pain index, SS showed statistically significant differences in stretching group. And EO showed statistically significant differences in the intergroup analysis. Conclusions: Both exercise could improve symptoms of fibromyalgia but showed no significantly better efficiency with intergroup analysis. Only some balance function was improved with core muscle strengthening exercise with significant difference. Our study presents preliminary results regarding the comparison between both exercises for fibromyalgia through a randomized controlled trial.